Therapeutic benefit of the dual ALK/FAK inhibitor ESK440 in ALK-driven neuroblastoma - Seema Chugh; Jean C. Tien; Jennifer Hon; Carson Kenum; Rahul Mannan; Yunhui Cheng; Chi Chiang Li; Zainab I. Taher; Andrew D. Delekta; Pushpinder Singh Bawa; Ingrid J. Apel; Stephanie J. Miner; et al. (Neoplasia: An International Journal for Oncology Research)
Neuroblastoma (NB) is a predominantly pediatric cancer with greater than 90% of cases arising in children under the age of five. More than half of patients have metastases detected at diagnosis, and high-risk disease is associated with five-year survival rates of only 50–60 %. Standard therapy involves highly toxic chemotherapy, surgery, radiation, and immunotherapy, and less toxic, more specific targeted therapies are urgently needed. Genomic studies have identified common driver aberrations in high-risk NB, such as MYCN amplification. In addition, a proportion of high-risk patients harbor amplification or activating mutations in anaplastic lymphoma kinase (ALK), and co-occurrence of ALK mutations and MYCN amplification have been associated with aggressive disease. In this study, we analyzed the efficacy of a Phase Ia-cleared, orally bioavailable dual ALK and focal adhesion kinase (FAK) inhibitor, ESK440, in multiple preclinical NB models. ESK440 potently inhibited proliferation of NB cell lines, with increased sensitivity in cell lines harboring ALK aberrations. ALK, FAK, and downstream target activation were rapidly decreased upon ESK440 treatment, and this was associated with impaired cellular migration and invasion. Importantly, ESK440 treatment also decreased MYCN levels. NB cell line and patient-derived xenograft studies showed significant reduction in tumor growth in ESK440-treated mice with no signs of toxicity. In certain NB models, ESK440 showed comparable or enhanced efficacy to lorlatinib, another clinical ALK inhibitor, and a lorlatinib-resistant cell line (COG-N-561 LR) retained sensitivity to ESK440. These preclinical results indicate that ESK440 is a promising targeted agent for ALK-driven NB and support future clinical studies to evaluate its efficacy in NB patients.